The languages of the Amazon - q (Oxford : Oxford University Press, 2012)
This guide and introduction to the extraordinary range of languages in Amazonia includes some of the most fascinating in the world and many of which are now teetering on the edge of extinction.
Description based on online resource; title from PDF title page (viewed on May 15, 2012).
Includes bibliographical references.
Keywords: Indians of South America -- Amazon River Region -- Languages